IMPLEMENTASI KEBIJAKAN MONETER DALAM MENGENDALIKAN JUMLAH UANG BEREDAR TERHADAP PENGANGGURAN DI INDONESIA - Agnes Monica Sianipar; Enjel Widia Sari Gea; Ian Josephan Saragih (CV. Denasya Smart Publisher, 2024)
This study examines the use of Bank Indonesia's monetary policy to control the money supply (JUB) and its impact on the unemployment rate in Indonesia. The objectives of this study are to: (1) evaluate Bank Indonesia's use of monetary policy to control money supply from 2014 to 2023; and (2) investigate how controlling money supply impacts the unemployment rate in Indonesia. The main focus of the study is to determine how effective Bank Indonesia's monetary policy is in managing JUB as a tool to reduce unemployment. Secondary data from the period 2014-2023 which includes data on unemployment rate and JUB were analyzed through simple regression analysis method and quantitative descriptive approach. The results of the analysis show that, with a correlation coefficient of 0.063 and an influence contribution of only 0.4%, there is a very weak and insignificant relationship between money supply and unemployment rate. According to the regression equation Y = 5.748 + 5.971X, every 1% increase in money supply will increase unemployment by 5.971. This finding suggests that Bank Indonesia's monetary policy in controlling the money supply.